Commitment. - Adorno, Theodor W.; Chomsky, Noam; Diederichsen, Diedrich; Lambrecht, Luk; Leemans, Koen; de Wolf, Hans Maria (Mechelen : De Garage, ruimte voor actuele kunst Mechelen, 2007)
Alys, Francis ; Andre, Carl ; Atelier van Lieshout ; Brey, Ricardo ; Broodthaers, Marcel ; Buren, Daniel ; Dekyndt, Edith ; Denicolai, Simona ; Durham, Jimmie ; Garaicoa, Carlos ; Garcia Torres, Mario ; Haacke, Hans ; Kippenberger, Martin ; Knight, John ; Maes, Ives ; De Mot, Geert ; Paci, Adrian ; Provoost, Ivo ; Sala, Anri ; Schütte, Thomas ; Tayou, Pascale Marthine ; Xhafa, Sislej
Nederlands
Engels
Exhibition. Commitment. De Garage, ruimte voor actuele kunst Mechelen. 24.02.2007 - 01.04.2007
boek